Phase velocity mapping through a NiTi stent with different levels of stenosis - Holton, Andrea D.; Venugopalan, Ramakrishna; Anayiotos, Andreas (My University, 2003)
Magnetic Resonance Imaging has the potential to become the new gold standard in the management of cardiovascular disease, particularly in the assessment of arterial lesions and post-intervention restenosis. NiTi stents exhibit superior MRI compatibility and allow direct MR imaging through the stented area. In the present study, pulsatile in-vitro flow measurements were obtained by Magnetic Resonance Phase-Velocity mapping (MR-PVW) through a nickel-titanium alloy stent with different grades of stenosis: a) 75%, 90% (symmetric) and 50% (asymmetric). The results showed clear visibility of the lumen through the stent/stenosis when compared with independent calculations of flow. The detection and evaluation of instent restenosis using these techniques could provide a non-invasive means of screening for further management of patients.
Keywords: Cardiovascular system; Flow meters; Magnetic resonance imaging